From Materials to Devices: Graphene toward Practical Applications. Issue 10 (25th August 2022) - Yang, Yi; Wei, Yuhong; Guo, Zhanfeng; Hou, Weiwei; Liu, Yingjie; Tian, He; Ren, Tian‐Ling
Abstract: Graphene, as an emerging 2D material, has been playing an important role in flexible electronics since its discovery in 2004. The representative fabrication methods of graphene include mechanical exfoliation, liquid‐phase exfoliation, chemical vapor deposition, redox reaction, etc. Based on its excellent mechanical, electrical, thermo‐acoustical, optical, and other properties, graphene has made a great progress in the development of mechanical sensors, microphone, sound source, electrophysiological detection, solar cells, synaptic transistors, light‐emitting devices, and so on. In different application fields, large‐scale, low‐cost, high‐quality, and excellent performance are important factors that limit the industrialization development of graphene. Therefore, laser scribing technology, roll‐to‐roll technology is used to reduce the cost. High‐quality graphene can be obtained through chemical vapor deposition processes. The performance can be improved through the design of structure of the devices, and the homogeneity and stability of devices can be achieved by mechanized machining means. In total, graphene devices show promising prospect for the practical fields of sports monitoring, health detection, voice recognition, energy, etc. There is a hot issue for industry to create and maintain the market competitiveness of graphene products through increasing its versatility and killer application fields. Abstract : Large‐scale, low‐cost, high‐quality, and excellent‐performance of raw graphene material are important factors that impact its industrialization development. Based on the excellent mechanical, electrical, thermo‐acoustical, optical, and other physical and chemical properties of graphene, it has made a great progress in the development of mechanical sensors, microphone, sound source, electrophysiological detection for sports monitoring, health detection, voice recognition, etc.